Thermal stability of rare earth-pysz thermal barrier coating with high-resolution transmission electron microscopy - Mahalingam S.; Manap A.; Yunus S.M.; Afandi N. (MDPI AG, 2023)
Durability of a thermal barrier coating (TBC) depends strongly on the type of mixed oxide in the thermally grown oxide (TGO) of a TBC. This study aims on discovering the effect of thermal stability in the TGO area containing mixed oxides. Two different bondcoats were studied using high-resolution transmission electron microscopy: high-velocity oxygen fuel (HVOF) and air-plasma spray (APS), under isothermal and thermal cyclic tests at 1400?C. The HVOF bondcoats were intact until 1079 cycles. In comparison, APS failed at the early stage of thermal cycling at 10 cycles. The phase transformation of topcoat from tetragonal to the undesired monoclinic was observed, leading to TBC failure. The results showed that the presence of transient aluminas found in HVOF bondcoat helps in the slow growth of ?-Al2O3 . In contrast, the APS bondcoat does not contain transient aluminas and transforms quickly to ?-Al2O3 along with spinel and other oxides. This fast growth of mixed oxides causes stress at the interface (topcoat and TGO) and severely affects the TBC durability leading to early failure. Therefore, the mixed oxide with transient aluminas slows down the quick transformation into alpha-aluminas, which provides high thermal stability for a high TBC durability. 2020 by the authors. Licensee MDPI, Basel, Switzerland.